Unraveling Talent Management A Key Driver for Organizational Performance Enhancement - Abdul Haris Muchtar; Atikah Salimah; Muhammad Ulil Abshar As Shofy (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study analyzes the urgency of talent management as a strategic driver in improving organizational performance amidst increasingly intense competition. Talent management plays a central role in optimizing human resource potential to support organizational success and strengthen sustainable competitive advantage. The primary objective of this study is to identify and assess the significant contribution of talent management practices to improving organizational performance through theoretical and conceptual approaches. The research method used is a qualitative literature study approach, namely through a systematic review of relevant literature on the strategies, processes, and implications of talent management. Data sources include scientific journals, books, and previous research reports discussing the theory and implementation of talent management in various types of organizations, both public and private sectors. The results of the study indicate that effective talent management—encompassing the process of identifying, developing, and retaining high-potential individuals—has a significant impact on increasing productivity, job satisfaction, and employee loyalty. Furthermore, talent management practices integrated with the organization's strategic objectives have been shown to encourage innovation, increase competitiveness, and strengthen the organization's adaptability to the dynamics of a complex business environment. The research findings also indicate that talent management functions not only operationally in managing human resources, but is also a strategic component that determines organizational sustainability. Thus, organizations that are able to implement talent management holistically and sustainably will be better prepared to face global challenges, while achieving competitive advantages that are oriented towards long-term performance.